المنهج الأنثروبولوجي وأدواته بين النظري والتطبيق - خواني, خالد (جامعة الوادي - University of Eloued, 2021)
يعتبر المنهج الأنثروبولوجي من البحوث الكيفية، ويعتمد أساسا على الدراسات الميدانية لأن دراسة الجانب الاجتماعي أو الثقافي لأي مجتمع يفرض على الباحث التقرب من عينة الدراسة ومعايشتها. يضع الأنثروبولوجي عامة تصورات الدراسة الأساسية بعد نزوله إلى حقل الدراسة حتى لا يصطدم مع واقع لا يعكس ميولاته البحثية، أو يقع في تناقضات لا تخدم الدراسة. يهدف الباحث في هذه الدراسة إلى إبراز الأدوات المستخدمة في الدراسات الأنثروبولوجية، وقد يقع الباحث في اشكال كيفية تطبيق هذه الأدوات خاصة أثناء استخدامه للمقابلة أو الملاحظة أو تحليل الصور التي التقطها عن موضوع الدراسة. كما تستلزم الضرورة البحثية في العديد من الحالات استخدام أكثر من أداة للإلمام بحيثيات أي دراسة ذات الطابع الأنثروبولوجي. أدرجنا في ختام الدراسة نماذج تطبيقية لدراسات أنثروبولوجية تبين الأدوات المستخدمة والنتائج المستخلصة. The anthropological approach is considered as qualitative research, and it mainly depends on field studies, because to study the social or cultural aspect of a society, the researcher must approach and live the daily life of this society. The anthropologist generally defines the basic concepts of his research after a field study so that it is realistic and does not contradict his research trends. The researcher aims in this study to highlight the tools used in anthropological studies, and the anthropologist may have problems how to apply these tools, especially when using the interview, observation or analysis of photos taken on the subject of the study. in many cases anthropological studies require the use of more than one tool to become familiar with the merits of the study. At the end of the study, we included models applied for anthropological studies showing the tools used and the results obtained. The anthropological approach is considered as qualitative research, and it mainly depends on field studies, because to study the social or cultural aspect of a society, the researcher must approach and live the daily life of this society. The anthropologist generally defines the basic concepts of his research after a field study so that it is realistic and does not contradict his research trends. In this study, the researcher aims to highlight the tools used in an anthropological study, because in many cases anthropological study requires the use of more than one tool to achieve the results that serve the objectives of the study.
The anthropological approach and its tools between theory and practice
مقال
Keywords: أنثروبولوجيا، منهج أنثروبولوجي، منهج، منهجية، أدوات المنهج الأنثروبولوجي; anthropology, anthropological method, method, methodology, the tools of the anthropological method